Intracellular cysteine oxidation is modulated by aquaporin‐8‐mediated hydrogen peroxide channeling in leukaemia cells. (15th November 2016) - Vieceli Dalla Sega, Francesco; Prata, Cecilia; Zambonin, Laura; Angeloni, Cristina; Rizzo, Benedetta; Hrelia, Silvana; Fiorentini, Diana
Abstract: The modulation of H2 O2 production by NADPH oxidase (Nox), on vascular endothelial growth factor (VEGF) stimulation, affects the redox signaling linked to cancer cell proliferation. H2 O2 signal transduction involves reversible oxidation of thiol proteins, leading to the formation of cysteine sulfenic acids, responsible for the temporary inactivation of many phosphatases. These events imply that H2 O2 reaches its intracellular targets. As Aquaporin‐8 (AQP8) has been demonstrated to funnel Nox‐produced H2 O2 across the plasma membrane, this study aims to elucidate the role of AQP8 in the redox signaling occurring in human leukaemia B1647 cells that constitutively produce VEGF. AQP8 overexpression or silencing resulted in the modulation of VEGF ability of increasing or decreasing, respectively, H2 O2 intracellular level. Moreover, data obtained by a dimedone‐based immunochemical method for sulfenic acid detection demonstrate that the expression of AQP8 can modulate the amplitude of downstream events, altering the activity of redox‐sensitive targets. In particular, AQP8 affected VEGF‐induced redox signaling by increasing the sulfenation of the tumor suppressor PTEN, which resulted in its inactivation and, in turn, caused Akt activation. Therefore, the dimedone‐based method for easily monitoring cellular protein sulfenation allowed to demonstrate, for the first time, the role of AQP8 on the fine tune of cysteine oxidation in target proteins involved in leukaemia cell proliferation pathways. © 2016 BioFactors, 43(2):232–242, 2017